Profile of IL-2, IL-4, IL-10, IFN- ? , TNF- ? and KC-like cytokines in pregnant bitches - Feliciano, M.a.r.; Silva, A.s.l.; Crivelaro, R.m.; Oliveira, M.e.f.; Coutinho, L.n.; Vicente, W.r.r. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The aim of this study was to determine the profile of IL-2, IL-4, IL-10, IFN-γ, and TNF-α cytokines and KC-like cells (natural killer) in pregnant bitches, unpublished values for the species. A total of 27 females of the Shi Tzu, Pug, English Bulldog and French breeds, weighing 4-20kg and aged 4-6 years were used. Blood samples were collected from bitches during the anestrous and on the 2nd, 5th, 6th, 7th and 8th week of pregnancy. Serum levels of cytokines were measured by panel MILLIPLEX MAP (CCYTO-90K, MILLIPORE, Billerica, Massachusetts, USA) validated for dogs. Twenty four females showed physiological pregnancy and three bitches showed pathological pregnancy. There was no difference between cytokine values during anestrous and gestational weeks of bitches (P>0.05). However, it was possible to verify the physiological behavior of serum levels during modulation of immune response in the gestational process of animals. In animals with gestational disorders, abnormal values for IL-2, IL-4 and INF-y were noted. It was concluded that serum levels of cytokines evaluated in pregnant bitches can help the better understanding of physiological and pathological gestational processes and correlated immunology in this species.

Objetivou-se por meio deste estudo determinar o perfil das citocinas IL-2, IL-4, IL-10, IFN-γ, TNF-α e células KC-like (natural killer) em cadelas gestantes, valores que são inéditos para a espécie. Foram utilizadas 27 fêmeas das raças Shi-tzu, Pug, Bulldog Inglês e Francês, pesando de 4 a 20 kg e com idade entre quatro e seis anos. Foram coletadas amostras sanguíneas das cadelas durante o anestro e na segunda, quinta, sexta, sétima e oitava semanas gestacionais. Os níveis séricos de citocinas foram dosados pelo painel MILLIPLEX MAP (CCYTO-90K, MILLIPORE, Billerica, Massachusetts, EUA) validado para cães. Vinte e quatro fêmeas apresentaram gestação fisiológica e três cadelas, gestação patológica. Não foi verificada diferença entre os valores das citocinas durante anestro e nas semanas gestacionais das cadelas (P>0,05). Entretanto, foi possível verificar o comportamento fisiológico dos níveis séricos durante a modulação da resposta imune no processo gestacional dos animais. Verificaram-se, nos animais com afecções gestacionais, valores alterados para IL-2, IL-4 e INF-y. Pôde-se concluir que os valores séricos das citocinas avaliadas, nas cadelas gestantes, podem auxiliar no maior conhecimento dos processos fisiológicos e patológicos da gestação, correlacionados à imunologia, nessa espécie.
Perfil de citocinas IL-2, IL-4, IL-10, IFN-?, TNF-? e células KC-like em cadelas gestantes
Keywords: cão; imunidade; gestação; dog; immunity; pregnancy